2019
DOI: 10.1107/s1600576719007568
|View full text |Cite
|
Sign up to set email alerts
|

Local orientational order in self-assembled nanoparticle films: the role of ligand composition and salt

Abstract: An X-ray cross-correlation study of the local orientational order in selfassembled films made from PEGylated gold nanoparticles is presented. The local structure of this model system is dominated by four-and sixfold order. Coadsorption of shorter ligands in the particle's ligand layer and variation of salt concentration in the suspension prior to self-assembly result in a change of local orientational order. The degree of sixfold order is reduced after salt addition. This decrease of order is less pronounced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In order to resolve the superlattice structure in detail, we performed the X-ray cross correlation analysis (XCCA), 49,50 which has been recently demonstrated to be a valuable tool to access structural information of crystalline materials beyond convectional pair correlation SAXS analysis. 36,[51][52][53][54][55]22 The details of the XCCA method are described in Ref. 56.…”
mentioning
confidence: 99%
“…In order to resolve the superlattice structure in detail, we performed the X-ray cross correlation analysis (XCCA), 49,50 which has been recently demonstrated to be a valuable tool to access structural information of crystalline materials beyond convectional pair correlation SAXS analysis. 36,[51][52][53][54][55]22 The details of the XCCA method are described in Ref. 56.…”
mentioning
confidence: 99%
“…In a follow‐up study, the authors reported a dependence of the local orientational order of the assembled films on the ligand composition. [ 132 ] Moreover, the addition of salt further reduced the order of the films due to screening of the charged particles during the assembly, suggesting a complex symmetry‐selective assembly process.…”
Section: X‐ray Scattering Methodsmentioning
confidence: 99%
“…[ 120 ] Order formation upon drying is thermodynamically favored for nearly any NP shapes, so it should be kept in mind that even dried NP films and materials that would not be considered “crystalline” but rather heterogenous and disordered at first sight, often feature some degree of local, sometimes hidden, order. [ 130–132 ] For many shapes, formation of crystalline superstructures can be thermodynamically even more favorable than for spheres, [ 133–135 ] e.g., perovskite nanocrystals with a cubic structure are known to crystallize readily. [ 109 ]…”
Section: Self‐assembly Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The particle concentration was 500 nM corresponding to a volume fraction of about 1 vol% AuNC. This system is known to selfassemble after solvent evaporation 26,27 and is supposed to form a superlattice around p ≈ 3000 bar 22 .…”
Section: Sample Preparationmentioning
confidence: 99%